2012
DOI: 10.5455/medarh.2012.66.364-368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Treatment with L-thyroxin on Glucose Regulation in Patients with Subclinical Hypothyroidism

Abstract: The normalization of TSH resulted in decrease of level of fasting insulin, fasting and postprandial glucose, CRP and lipids. Higher CRP associated with fasting hyperinsulinemia before insulin resistance has been evidenced in most patients with SH. These data support an important role of treatment of SH in support of glucose regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…al (1996) (11), found that the diastolic dysfunction is present in both sub-clinical and over hypothyroidism while pericardial effusion is seen only in overt hypothyroidism and mean serum cholesterol is significantly raised in oth sub-clinical and overt hypothyroidism with respect to control group. Simmilar results presented by B&H authors (12, 13). …”
Section: Discussionmentioning
confidence: 84%
“…al (1996) (11), found that the diastolic dysfunction is present in both sub-clinical and over hypothyroidism while pericardial effusion is seen only in overt hypothyroidism and mean serum cholesterol is significantly raised in oth sub-clinical and overt hypothyroidism with respect to control group. Simmilar results presented by B&H authors (12, 13). …”
Section: Discussionmentioning
confidence: 84%
“…They found a positive correlation between HbA1c and TSH and positive correlation between HbA1c and insulin. Thus they concluded that normalised TSH levels will result in decreased levels of fasting insulin, FBS, PPBS and HbA1c Edina Bilic-Komarica et al (3) conducted a study to understand the effects of treatment of L-thyroxine on glucose regulation in patients with subclinical hypothyroidism. The study group consisted of 100 patients, out of which 38 patients were diabetic.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, other authors have showed a significant worsening of glucose levels at the followup supporting the role of subclinical hypothyroidism in glucose regulation. 23 In conclusion, in CHD patients with subclinical hypothyroidism, most of whom had a thyroidstimulating hormone concentration between 5 and 10 mIU/L, no changes were seen in serum thyroxine, glucose, cholesterol, or C-reactive protein concentrations before and after the follow-up regardless of whether they were or not under thyroid hormone replacement therapy. Although our small sample size, non-randomised design, can limit the result of our study we must consider a proper follow-up, especially in CHD patients with thyroid-stimulating hormone concentration above 10 mIU/L, with heart failure, 24 or at an increased risk for cardiovascular events.…”
Section: Type Of Congenital Malformations Patientsmentioning
confidence: 74%